Inhibitory effects of endomorphin-2 on excitatory synaptic transmission and the neuronal excitability of sacral parasympathetic preganglionic neurons in young rats - Chen, Ying-Biao; Huang, Fen-Sheng; Fen, Ban; Yin, Jun-Bin; Wang, Wei; Li, Yun-Qing (Frontiers in Cellular Neuroscience, 2015)
The function of the urinary bladder is partly controlled by parasympathetic preganglionic neurons (PPNs) of the sacral parasympathetic nucleus (SPN). Our recent work demonstrated that endomorphin-2 (EM-2)-immunoreactive terminals form synapses with µ-opioid receptor (MOR)-expressing PPNs in the rat SPN. Here, we examined the effects of EM-2 on excitatory synaptic transmission and the neuronal excitability of the PPNs in young rats using a whole-cell patch-clamp approach. PPNs were identified by retrograde labeling with the fluorescent tracer TMR. EM-2 (3 µM) markedly decreased both the amplitude and the frequency of the spontaneous and miniature excitatory postsynaptic currents (sEPSCs and mEPSCs) of PPNs. EM-2 not only decreased the resting membrane potentials (RMPs) in 61.1% of the examined PPNs with half-maximal response at the concentration of 0.282 µM, but also increased the rheobase current and reduced the repetitive action potential firing of PPNs. Analysis of the current–voltage relationship revealed that the EM-2-induced current was reversed at -95 ± 2.5 mV and was suppressed by perfusion of the potassium channel blockers 4-aminopyridine (4-AP) or BaCl2 or by the addition of GDP-β-S to the pipette solution, suggesting the involvement of the G-protein-coupled inwardly rectifying potassium (GIRK) channel. The above EM-2-invoked inhibitory effects were abolished by the MOR selective antagonist D-Phe-Cys-Tyr-D-Trp-Orn-Thr-Pen-Thr-NH2 (CTOP), indicating that the effects of EM-2 on PPNs were mediated by MOR via pre- and/or post-synaptic mechanisms. EM-2 activated pre- and post-synaptic MORs, inhibiting excitatory neurotransmitter release from the presynaptic terminals and decreasing the excitability of PPNs due to hyperpolarization of their membrane potentials, respectively. These inhibitory effects of EM-2 on PPNs at the spinal cord level may explain the mechanism of action of morphine treatment and morphine-induced bladder dysfunction in the clinic.